2015
DOI: 10.1097/brs.0000000000000799
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrinolytics Reduce Blood Loss in Adult Spinal Deformity Surgery

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 20 publications
2
40
0
1
Order By: Relevance
“…These inconsistent results may warrant more number of future refined studies, despite most high level of evidence studies favor the use of TXA in spinal surgery5,24,25). Most studies showed tendency toward less postoperative bleeding in TXA group with or without statistical significance1,20,24,25). Present study also demonstrated less postoperative drain amount in TXA group without reaching statistical significance.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These inconsistent results may warrant more number of future refined studies, despite most high level of evidence studies favor the use of TXA in spinal surgery5,24,25). Most studies showed tendency toward less postoperative bleeding in TXA group with or without statistical significance1,20,24,25). Present study also demonstrated less postoperative drain amount in TXA group without reaching statistical significance.…”
Section: Discussionmentioning
confidence: 60%
“…Previous investigator did not find any significant differences in intraoperative blood losses or transfusion requirements between TXA and control groups in patients with spinal deformity17,20). Baldus and colleagues concluded in their study in patients undergoing lumbar pedicle subtraction osteotomy that TXA use did not decrease surgical bleeding or intraoperative transfusion amount whereas using aprotinin did1).…”
Section: Discussionmentioning
confidence: 94%
“…Multiple studies have demonstrated the potential effectiveness of intraoperative antifibrinolytic therapy in significantly reducing blood loss (A. Soroceanu et al, unpublished data). 9,36,65 In addition, a recently published application of rotational thromboelastometry-guided blood product management to major spine procedures suggests that this technology may aid in reducing blood loss, blood product use, and cost. 31 Infections accounted for 9% of all major complications, and deep wound infection was the most common infection.…”
Section: Discussionmentioning
confidence: 99%
“…Blood loss during ASD surgery may be greater than 4 L in cases involving osteotomy, 7 potentially leading to organ damage, coagulopathy, infections, longer hospital stays, and higher costs. 16 Recently, a double-blinded randomized controlled trial showed that antifibrinolytics significantly reduced blood loss in posterior ASD surgery compared with placebo. 16 Not surprisingly, coagulopathy was the strongest independent factor associated with development of any postoperative complication (OR 4.2).…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, a double-blinded randomized controlled trial showed that antifibrinolytics significantly reduced blood loss in posterior ASD surgery compared with placebo. 16 Not surprisingly, coagulopathy was the strongest independent factor associated with development of any postoperative complication (OR 4.2). This was followed by revision procedures (also associated with higher blood loss) 23 and complex procedures.…”
Section: Discussionmentioning
confidence: 99%